Urgensi Tata Kelola Dokumentasi Hukum Di Sektor Pendidikan Tinggi Melalui Sistem Informasi JDIH Perguruan Tinggi - Suharto, Miko Aditiya; Maria Novita Apriyani, Maria (Fakultas Hukum Universitas Mulawarman, 2024)
JDIHN contains legal documents stored digitally in an electronic database that can be accessed from anywhere by the general public. Based on Presidential Decree 33/2012, universities are also ordered to form JDIH in their respective environments. Legal regulations and policies must be formed and socialized in each Higher Education Units so that the teaching and learning process runs well. However, many of the legal regulations and policies made in this higher education environment, if analyzed using legal science, have many administrative and substantive defects. In order to achieve the goals of National legal development and as an effort to prevent disharmonization of legal regulations and policies vertically and horizontally within Higher Education units. This research is a normative legal research type, using a statute approach and a conceptual approach. JDIH in the implementation of Higher Education is expected to be able to minimize disharmonization of regulations and policies that occur in local universities so that they can be minimized or resolved. This method is also a means of realizing the principle of transparency in public services in order to realize good governance and achieve the goals of national legal development. The implementation of JDIH integration starting from each Higher Education Institutions as a member to the Ministry of Education and Culture's JDIH as coordinator, which then continues with integration into BPHN, needs to be regulated in a Ministerial Regulation so that there is no overlap in The authority